Effect of exogenous calcium on post-thaw growth recovery and subsequent plant regeneration of cryopreserved embryogenic calli of Hevea brasiliensis (Muell. Arg) - Lardet Ludovic; Carron Marc-Philippe; Dessailly Florence; Martin Florence; Montoro Pascal (Plant Cell Reports, 2007)
A reliable cryopreservation technique was developed for friable embryogenic callus lines of Hevea brasiliensis. The study showed that reducingthe CaCl2 concentration of the pre-culture medium from 9mM to 1 or 0 mM CaCl2 before cryopreservation promoted post-thaw callus growth, 1 mM being the optimum CaCl2 concentration for embryo regeneration. Post-thaw callus proliferation decreased in line with the increase of planted callus weight. The effect of cryopreservation was assessed on 39 independent lines showing that cryopreservation did not affect embryogenic and plant regeneration for a majority of lines. The decrease in CaCl2 concentration of the pre-culture medium and the endogenous calcium content of the calli. It also highlighted the implication of tissue calcium content in cryotolerance. Callus water status and the different ways by which calcium could prevent cryoinjury is also discussed.
Keywords: Calcium; Cryopreservation; Embryogenic culture; Pre-culture